(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Today, a foreign language is not just a part of the culture of a certain nation, but it is also the key to success and a successful future career for students. The main learning strategy is a personality-oriented approach that puts the child’s personality, abilities, inclinations and needs at the center of the educational process. All this can be implemented on the basis of new educational technologies.